LAYANAN PENYEDIAAN JASA TRANS METRO PEKANBARU OLEH PERUSAHAAN DAERAH PEMBANGUNAN TAHUN 2014 - Jermi "; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Trans Metro is one of the transport is managed by the Regional Development Company of Pekanbaru in order to meet the needs of the public transportation services in the city of Pekanbaru. Society can use these transport services to facilitate their activities in travel. But Trans Metro Pekanbaru in providing transportation services not in accordance with the expectations that people want. It is seen from there were few complaints from the public. This study aimed to find out how exactly the Trans Metro Pekanbaru services and to determine the factors that affect transport services on Trans Metro Pekanbaru using five indicators in public service namely Physical Evidence, Reliability, Responsiveness, Assurance and Empathy. This study used a qualitative approach and descriptive research type with data collection techniques do is interview and documentation. The results of this study, that the Service Provisioning Services Trans Metro Pekanbaru by the Regional Development Company has not done well. It can be seen from some of the factors that affect, among others, limited human resources available, is still a lack of infrastructure and also the lack of community participationKeywords : Public Services, Local Transportation, Local Company